2013
DOI: 10.1161/hypertensionaha.111.203489
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-376c Impairs Transforming Growth Factor-β and Nodal Signaling to Promote Trophoblast Cell Proliferation and Invasion

Abstract: The online-only Data Supplement is available with this article at http://hyper.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 49 publications
7
140
0
1
Order By: Relevance
“…PET is a major disorder of pregnancy characterized by an increased maternal inflammatory response and vascular dysfunction, 14 affecting placentation, trophoblast proliferation, invasion, 15 and apoptosis. The current study demonstrated that NHP women and women with GVC displayed similar levels of circulating MVs, which is in accordance with our previous report 10 and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…PET is a major disorder of pregnancy characterized by an increased maternal inflammatory response and vascular dysfunction, 14 affecting placentation, trophoblast proliferation, invasion, 15 and apoptosis. The current study demonstrated that NHP women and women with GVC displayed similar levels of circulating MVs, which is in accordance with our previous report 10 and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were carried out in The People's Republic of China [33e35, 37,40,42,43,45,50,52e58,63,64,67,69,72e74], the USA [32,46e48,51,54,61,70,71], South Korea [49], Canada [50,60], Japan [62], Turkey [65], Chile [66], Germany [68], Hungary [59], Switzerland [36], Norway [38], Italy [39], Spain [41], and the Czech Republic [44] (see Table 1 for details).…”
Section: Resultsmentioning
confidence: 99%
“…Fu et al [50] found that miR-376c is downregulated in preeclamptic placenta samples and that this targets ALK7 and ALK5, which are molecules important to the Nodal signaling pathway. The study also confirmed that Nodal and ALK7 levels are upregulated in preeclamptic placenta samples [50]. Therefore, downregulation of miR-376c in the preeclamptic placenta results in higher ALK7 expression and this then results in the enhancement of Nodal signaling (Fig.…”
Section: The Roles Of Mirnas In Trophoblast Proliferation Survival Amentioning
confidence: 99%
“…To establish miR-376c as a predictive or diagnostic biomarker of preeclampsia, the study by Fu and colleagues 7 requires confirmation in independent and larger cohorts. Already at this stage, however, it provides a better understanding of the processes leading to impaired trophoblast invasion…”
Section: April 2013mentioning
confidence: 99%
“…Nevertheless, the available studies confirm dysregulation of miRNAs that play a role in the regulation of trophoblast cell invasion, such as miR-195 4 and miR-29b, 5 and mitochondrial function such as miR-210. 6 In this issue of Hypertension, 7 Fu and colleagues assess, in detail, one particular miRNA, miR-376c, and its expression and function in normal pregnancy and in preecampsia using a range of cellular assays, molecular manipulations, and patient materials. miR376c is expressed within a region of imprinted DNA on human chromosome 14, a region rich in noncoding RNA species, including an abundance of distinct miRNAs (http://www.ensembl.…”
mentioning
confidence: 99%